ANALYSIS OF THE EFFECTIVE TECHNOLOGY OF INCREASING THE CORROSION RESISTANCE OF CAST PARTS - Xayitboyev Qudratbek Anvarbek ugli (European Science Publishing, 2024)
Corrosion of cast parts is a significant concern in various industries, as it can lead to reduced component lifespan and safety hazards. This article explores the effective technologies used to enhance the corrosion resistance of cast parts. The study reviews various methods, including surface coatings, alloy composition modification, and heat treatment, and their impacts on corrosion resistance. It provides insights into the mechanisms underlying these techniques and their practical applications. The article concludes with the importance of considering the specific requirements of the application and the need for ongoing research in this critical field.
Keywords: Corrosion, critical area, automotive, aerospace, maritime, infrastructure, moisture, oxygen, corrosive agents, as electroplating, hot-dip galvanizing, powder coating, Alloy Selection, Surface Coatings, Surface Modification, Cathodic Protection, Environmental Control.